Oligothiophene molecular wires at graphene-based molecular junctions - Gao, Tingwei; He, Chunhui; Liu, Chenguang; Fan, Yinqi; Zhao, Cezhou; Zhao, Chun; Su, Weitao; Dappe, Yannick J; Yang, Li (Physical chemistry chemical physics : PCCP, 2021)
The use of graphene as a new type of electrode at molecular junctions has led to a renewal of molecular electronics. Indeed, the symmetry breaking induced by the graphene electrode yields different electronic behaviors at the molecular junction and in particular enhanced conductance for longer molecules. In this respect, several studies involving different molecular backbones and anchoring groups have been performed. Here in the same line, we consider oligopthiophene based hybrid gold-graphene junctions and we measure their electrical properties using the STM- I ( s ) method in order to determine their attenuation factor and the effect of specific anchoring groups. The results are supported by density functional theory (DFT) calculations, and exhibit a similar behavior to what is observed at alkane-based junctions. The electrical properties of oligopthiophene-based hybrid gold-graphene junctions were measured with the STM- I ( s ) method to determine the attenuation factor and effect of specific anchoring groups. It shows that graphene is an effective contact in forming nano-junctions.